Past riverine connectivity effects in population structure and distribution of an endemic freshwater fish from northeastern Brazilian rivers: Phylogeographic, taxonomic, and conservation implications - Oliveira-Silva, Leonardo [UNESP]; Batalha-Filho, Henrique; Camelier, Priscila; Zanata, Angela M. (Wiley, 2023)
The coastal basins of eastern Brazil are influenced by geomorphologic and climatic changes that caused river captures and temporary paleo-connections due to sea-level oscillations. These two events can lead to isolation and connection among coastal rivers and have a strong influence on the distribution of freshwater fishes in this region. Characidium bahiense is a small fish species with a wide distribution, ranging from the coastal basins of the North Group of the Northeastern Mata Atlântica ecoregion to São Francisco and Parnaíba ecoregions. The allopatric distribution of C. bahiense associated with the possible morphological and molecular variations among geographically isolated populations stimulated this study. Here, we use an integrative approach, encompassing morphological and mitonuclear data, and paleodrainage reconstruction to better understand the evolutionary history of C. bahiense and to test the putative effects of the current configuration of basins and historical drainage rearrangements on the genetic structuring of the species. Our mitochondrial data show that C. bahiense is not a monophyletic species since the specimens from one locality are more closely related to Characidium cf. lagosantense than to other populations of C. bahiense. Multilocus analyses, however, recovered the monophyly of this species, although the molecular delimitation method considers each mitochondrial DNA lineages as a separated species. Overall, the morphological data revealed some intraspecific overlapping variation, suggesting that all specimens of C. bahiense are conspecific. Molecular analyses combined with geomorphological information suggest that the current distribution of C. bahiense is the result of climate change that directly affected river flow dynamics and recent riverine captures during the Pleistocene. The use of multiple data sources not only provides a more reliable interpretation of the evolutionary history of a species, but can also avoid arbitrary taxonomic decisions. Future phylogeographic studies involving other freshwater fish species with a similar distribution to C. bahiense are necessary to assist in understanding the scenarios presented here.
Keywords: Characidium; multilocus approach; Neotropical freshwater fishes; Pleistocene; river captures